2022
DOI: 10.1186/s12866-022-02606-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the best technic to dislodge Staphylococcus epidermidis biofilm on medical implants?

Abstract: Background Bacterial biofilm can occur on all medical implanted devices and lead to infection and/or dysfunction of the device. In this study, artificial biofilm was formed on four different medical implants (silicone, piccline, peripheral venous catheter and endotracheal tube) of interest for our daily clinical and/or research practice. We investigated the best conventional technic to dislodge the biofilm on the implants and quantified the number of bacteria. Staphylococcus epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…However, the ESCMID Biofilm guidelines published in 2015 clearly stated that regarding patients with ETT biofilm, “mucus from within the ETT can be aspirated and cultured to identify ETT pathogens in ETT biofilms that may have caused VAP 35 ”. Moreover, our group recently demonstrated a clear superiority of the chemical treatment dithiothreitol (Digest-EUR) over sonication for the dislodgement of Staphylococcus epidermidis biofilm on ETT 24 . Based on both our recent experience and the ESCMID Biofilm guidelines, the present work used a mucus reagent (Digest-EUR) for the microbiological processing of biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ESCMID Biofilm guidelines published in 2015 clearly stated that regarding patients with ETT biofilm, “mucus from within the ETT can be aspirated and cultured to identify ETT pathogens in ETT biofilms that may have caused VAP 35 ”. Moreover, our group recently demonstrated a clear superiority of the chemical treatment dithiothreitol (Digest-EUR) over sonication for the dislodgement of Staphylococcus epidermidis biofilm on ETT 24 . Based on both our recent experience and the ESCMID Biofilm guidelines, the present work used a mucus reagent (Digest-EUR) for the microbiological processing of biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining half of the ETT sections (below- and above-the-cuff sections) were gently homogenized in a 20% Digest-EUR® solution (Eurobio Scientific, Les Ulis, France) for 15 min at 37 °C according to a previously described protocol 16 , 24 . After a few seconds of gentle shaking, an aliquot of the solution was then spread on different culture plates (trypticase soy agar, blood agar under aerobic and anaerobic atmospheres, Drigalski agar, chocolate agar with the addition of 5% CO 2 , and Sabouraud agar) incubated for 48 h at 37 °C, either pure or at 1/10 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…In 1981, a case report suggested a potential link between latent bacterial infection and capsular contracture [ 52 , 53 , 54 , 55 ]. Subsequent studies, spanning nearly two decades, further demonstrated the isolation of coagulase-negative bacteria Staphylococcus epidermidis from the implant or tissue in cases of capsular contracture [ 38 , 39 , 40 , 41 , 44 , 56 , 57 , 58 , 59 ]. The formation of S. epidermidis biofilms was investigated on differently textured silicone surfaces, revealing that rougher surfaces attract more bacteria and support thicker biofilm growth [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm originated as a defense mechanism for prokaryotes against too harsh conditions, it has garnered a lot of interest due to higher effect to public health, medicine, food and pharmaceutical industry. Structured groups of microbial cells attached together and collapsed in an extracellular matrix with different density and composition were defined as biofilms [3]. Biofilm considered as adaption mode which enable microbial cell to survive in hard conditions such as UV radiation, sudden changes in pH values and draining [4].…”
Section: Introductionmentioning
confidence: 99%